The ethics of medical involvement in torture: commentary - Hare, R M (1993)
Torture does need to be defined if we are to know exactly what we are seeking to ban; but no single definition will do, because there are many possible ones, and we may want to treat different practices that might be called torture differently. Compare the case of homicide; we do not want to punish manslaughter as severely as murder, and may not want to punish killing in self-defence at all. There are degrees of torture as of murder. Unclarities simply play into the hands of would-be torturers. Downie is unsuccessful in deriving the duty of doctors not to be involved in torture from an analysis of the word `doctor'. It may be contrary to the role-duty of doctors to participate in torture; but there might be other duties which overrode this role-duty. The right approach is to ask what principles for the conduct of doctors have the highest acceptance-utility, or, as Kant might have equivalently put it, what the impartial furtherance of everyone's ends demands. This approach yields the result that torture (suitably defined) should be banned absolutely. It also yields prescriptions for the conduct of doctors where, in spite of them, torture is taking place.